1978
DOI: 10.1002/1097-0142(197811)42:5<2177::aid-cncr2820420514>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

o,p′-DDD (mitotane) therapy of adrenal cortical carcinoma. Observations on drug dosage, toxicity, and steroid replacement

Abstract: Four patients with adrenal cortical carcinoma were treated with standard doses of o,p'-DDD. Plasma levels of o,p'-DDD and its metabolites o,p'-DDA and o,p'-DDE were measured. o,p'-DDD was measurable for up to 8 months after stopping therapy, and trace levels of metabolites were detectable at 18 months. Although 2 of 3 patients with measurable disease had objective tumor response and one patient achieved a complete response, severe drug toxicity occurred in all patients and signs of adrenal insufficiency occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

1980
1980
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(15 citation statements)
references
References 21 publications
1
11
0
3
Order By: Relevance
“…Recently, a retrospective study has highlighted the efficacy of mitotane therapy in CD treatment (Baudry et al 2012). Mitotane (o,p 0 -DDD), a derivative of the insecticide dichlorodiphenyltrichloroethane, has been widely used for treatment of advanced (unresectable, metastatic, or relapsed) adrenocortical carcinoma (ACC; Bergenstal et al 1960, Young et al 1973, Hogan et al 1978, Lughezzani et al 2010 and is increasingly used in adjuvant settings (Fassnacht et al 2012). Mitotane concentrations are associated with both efficacy and toxicity (Haak et al 1994, Terzolo et al 2000 and blood levels R14 mg/l predict ACC tumor response (Haak et al 1994, Hermsen et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a retrospective study has highlighted the efficacy of mitotane therapy in CD treatment (Baudry et al 2012). Mitotane (o,p 0 -DDD), a derivative of the insecticide dichlorodiphenyltrichloroethane, has been widely used for treatment of advanced (unresectable, metastatic, or relapsed) adrenocortical carcinoma (ACC; Bergenstal et al 1960, Young et al 1973, Hogan et al 1978, Lughezzani et al 2010 and is increasingly used in adjuvant settings (Fassnacht et al 2012). Mitotane concentrations are associated with both efficacy and toxicity (Haak et al 1994, Terzolo et al 2000 and blood levels R14 mg/l predict ACC tumor response (Haak et al 1994, Hermsen et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The endocrine data (Moolenaar et al, 1975;Hogan et al, 1978;Slooten et al, 1984). in predicting the tumor response to M, but also useful in predicting the occurrence of adverse effects of CNS toxicities due to the drug, as already reported .…”
Section: Case Report and Resultsmentioning
confidence: 88%
“…No standard has been established for treat-ment, and the overall prognosis has usually been poor. Mitotane (M) has been widely employed as the most promising adjuvant therapy (Hutter and Kayhoe 1966;Hoffman and Mattox 1972;Lubitz et al, 1973), and a few isolated cases demonstrated dramatic response to the drug (Dowing et al, 1974;Ostuni and Roginsky et al, 1975;Jabarak and Rice et al, 1981;Boven et al, 1984;Slooten et al 1984;Naruse et al, 1984;Hogan et al, 1978). Evaluation of the serum and subcutaneous M concentrations as a guide to M therapy have been tried (Moolenaar and von Seters 1975;Slooten et al, 1982Slooten et al, , 1984Hogan et al, 1978), but results are controversial.…”
mentioning
confidence: 99%
“…Häufiger gelingt eine Beeinflussung der pathologischen Hormonproduktion (30-70%). Eine Tumorregression wurde in unterschiedlichen Studien in einem Prozentsatz von 15-60% beobachtet [11,13,21,22,23,24,25,26,27,28,29,30]. Langsam wachsende Karzinome mit endokriner Aktivität sprechen offenbar eher an als rasch progrediente, undifferenzierte endokrin inaktive Tumoren.…”
Section: Medikamentöse Therapie Op'ddd (Mitotane)unclassified